The Aging-Inequality Nexus: The Domestic Savings Channel And Threshold Effects In Asia-Pacific Countries - affarudin, Muhammad Raees Shaik S (2024)
Income inequality has generally exhibited an increasing trend, albeit at varying rates among Asia-Pacific countries, during a concurrent boom in the elderly population. As such, the connection between the rising prevalence of the aging population and the slow progress in alleviating income inequality remains unclear. Moreover, there is a lack of empirical analysis focusing on domestic savings as a potential transmission mechanism within the aging-inequality nexus. To address these questions, this study sets forth three primary objectives. First, the study investigates whether a long-term relationship exists between aging and income inequality using the Augmented Autoregressive Distributed Lag (A-ARDL) bounds test. The key findings confirm that aging coexists with income inequality in advanced aging economies. Empirical evidence indicates that population aging exacerbates income inequality in Australia, New Zealand, Japan, and China. Conversely, the aging process in Hong Kong appears to moderate inequality. The second objective explores the role of domestic savings as a transmission mechanism in the relationship between aging and income inequality, while also considering the effects of social globalization. The results reveal that aging significantly influences savings behaviors in aged and super-aged countries. Australia, New Zealand, Japan, and China display a negative relationship between aging and savings, whereas Hong Kong shows a positive correlation between the older dependency ratio and domestic saving.